LEVERAGING TECHNOLOGY IN EDUCATION TRANSFORMATION, TO OPTIMIZE STUDENT LEARNING IN THE FUTURE - Wulandari, Shelinda Dita; Hadiwijaya, Munawwir (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
The use of technology in education has become a critical effort to improve the quality of student learning. With the advancement of technology, education has become more dynamic and participatory. In this journal, we will look at how technology can be used effectively to improve student learning. Given its significance, the use of technology in education in the modern period is becoming increasingly important. This publication also explores the role of technology in educational reform to improve student learning for the future. Computers, the internet, and mobile devices have all made it easier and more pleasurable for students to learn.